2021
DOI: 10.7717/peerj.11058
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of the behavior of two broadcast spawners, the sea urchinsStrongylocentrotus intermediusandMesocentrotus nudus, during mass spawning events in situ

Abstract: Background The spatial distribution of spawners and temporal parameters of spawning in motile invertebrates with external fertilization might influence reproductive success. However, to date, data on the prespawning and spawning behaviors of broadcast spawners in the field have been scarce and mostly qualitative. The present study was intended to clarify the behavioral adaptations of two sea urchin species, Strongylocentrotus intermedius and Mesocentrotus nudus, using quantitative analysis of their behavior du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Strongylocentrotus intermedius and Mesocentrotus nudus showed significant increases in their locomotion rate before and during spawning and the authors concluded that this synchronization was likely caused by the concentrations of phytoplankton (Zhadan et al, 2021). Nevertheless, the frequency of spawning in nature for each individual and whether it is synchronized among individuals remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strongylocentrotus intermedius and Mesocentrotus nudus showed significant increases in their locomotion rate before and during spawning and the authors concluded that this synchronization was likely caused by the concentrations of phytoplankton (Zhadan et al, 2021). Nevertheless, the frequency of spawning in nature for each individual and whether it is synchronized among individuals remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The sea urchin Arbacia punctulata in the Gulf of Mexico was also reported to have a lunar reproductive rhythm around the new moon during the summer months from May to July (Hernandez et al., 2022). Strongylocentrotus intermedius and Mesocentrotus nudus showed significant increases in their locomotion rate before and during spawning and the authors concluded that this synchronization was likely caused by the concentrations of phytoplankton (Zhadan et al., 2021). Nevertheless, the frequency of spawning in nature for each individual and whether it is synchronized among individuals remain unclear.…”
Section: Introductionmentioning
confidence: 99%